2009
DOI: 10.1021/jp809095q
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectral Properties of Ferrocene (Fc) in Ionic Liquid: 1-Butyl-3-methylimidazolium Triflimide, [BMIM][NTf2]. Concentration Effects

Abstract: Several earlier studies of the electrochemical oxidation of ferrocene (Fc) in room-temperature ionic liquids revealed an essentially nonlinear dependence of the oxidation current on the Fc concentration in its relatively dilute solutions, with its formally calculated diffusion coefficient strongly increasing with the concentration. Since no plausible mechanism leading to this very unusual finding had been proposed, our study of Fc solutions in 1-butyl-3-methylimidazolium triflimide, [BMIM][NTf(2)], was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 54 publications
5
31
0
Order By: Relevance
“…For the case of Fc in [BMIm][N(Tf) 2 ] the value determined by us at 20 • C, namely 2.9 × 10 −7 cm 2 s −1 , is in reasonable agreement with the literature values of 3.77 × 10 −7 cm 2 s −1 [45], measured at 26 • C. Higher temperature means lower viscosity and higher D values; it was reported that each two-degree shift results in 10% change of the IL viscosity [46], so that, taking into account this factor, the two values are almost the same. Note that recently, for the same probe and IL, Vorotyntsev measured at 20 • C a D value of 1.7 × 10 −7 cm 2 s −1 [46]. On the other hand, the D value determined by us for Fc in [BmPy][N(Tf) 2 ], namely 0.7 × 10 −7 cm 2 s −1 , is about three times smaller than the value 2.31 × 10 −7 cm 2 s −1 , measured by Compton's group [45].…”
Section: Gc-macrosupporting
confidence: 91%
“…For the case of Fc in [BMIm][N(Tf) 2 ] the value determined by us at 20 • C, namely 2.9 × 10 −7 cm 2 s −1 , is in reasonable agreement with the literature values of 3.77 × 10 −7 cm 2 s −1 [45], measured at 26 • C. Higher temperature means lower viscosity and higher D values; it was reported that each two-degree shift results in 10% change of the IL viscosity [46], so that, taking into account this factor, the two values are almost the same. Note that recently, for the same probe and IL, Vorotyntsev measured at 20 • C a D value of 1.7 × 10 −7 cm 2 s −1 [46]. On the other hand, the D value determined by us for Fc in [BmPy][N(Tf) 2 ], namely 0.7 × 10 −7 cm 2 s −1 , is about three times smaller than the value 2.31 × 10 −7 cm 2 s −1 , measured by Compton's group [45].…”
Section: Gc-macrosupporting
confidence: 91%
“…Fc sublimes relatively quickly at atmospheric temperature and pressure, [6,7] as well as in vacuo. [4,8] Ionic liquids (ILs) have also found widespread applications, particularly with respect to typically possessing extremely low vapour pressures, [9] wide electrochemical windows and inherent conductivity. [10] Their low vapour pressure has led to their application in in situ electrochemistry-XPS investigations, [11] as well as non-volatile electrolytes for gas sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is currently a heavy reliance on in situ reference couples, such as cobaltocenium j cobaltocene, [1] TMPD j TMPD + · and Ag( 0 ) j Ag I , [14] as well as a significant number of iron-based compounds, [1,15,16] although the use of ferrocene j ferrocenium [1,4,5,7,8,[15][16][17][18][19][20] appears to be especially prevalent. It has previously been observed that placing ILs in vacuo or under a flow of inert gas can result in the volatilisation of dissolved Fc, [4,7,8] and this fact has been partially attributed [8] to discrepancies in the literature regarding diffusion coefficient values, D, and the erroneous assumption that D is strongly related to Fc concentration. [1,8] The non-volatility of ILs encourages their application as thin films on the surfaces of electrodes [21] which can be problematic to characterise, and change with temperature, water content, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent works relate to the electrochemical and hydrodynamic behavior of organic and organometallic redox couples, such as tris(4-bromophenyl)amine (TBPA/TBPA + ), cobaltocene (Cc/Cc + ) and ferrocene (Fc/Fc + ) in RTILs [11][12][13][14][15][16][17][18]. In all cases, the diffusion coefficient of the studied electro-active species appears, irrespectively of ionic liquid, two orders of magnitude lower than that measured in a more conventional organic solvent.…”
Section: Introductionmentioning
confidence: 99%